EVALUASI STRATEGIS INVESTASI PENDIDIKAN DI MAN INSAN CENDEKIA KOTA BATAM DALAM PROGRAM CAMBRIDGE DAN IMPLIKASINYA TERHADAP PENGEMBANGAN SUMBER DAYA MADRASAH: Cambridge curriculum; Educational investment; Global competitiveness; Human resource development; Islamic school - Helena Rouhillahi; Sarmini; Ngaliman; Sri Yanti; Diana Titik Windayati (Universitas Batam, 2026)
This study aims to strategically evaluate the educational investment carried out by MAN Insan Cendekia Kota Batam through the implementation of the Cambridge Program since 2023, and to analyze its implications for the development of madrasah human and institutional resources. The program is considered an innovative step in integrating an international curriculum with Islamic values within a national education context. A descriptive qualitative approach was used, employing in-depth interviews, document analysis, and participatory observation involving teachers, students, and program managers. The findings reveal that the investment focuses on four key areas: (1) human resource development through teacher training, certification, and professional competency enhancement; (2) curriculum integration between the national and Cambridge syllabi and teaching materials; (3) provision of internationally standardized learning resources and facilities; and (4) the strengthening of academic culture and global networks. The program has brought about positive changes in classroom engagement, critical thinking skills, and the global competitiveness of students. However, challenges remain, including limited pedagogical mastery of the Cambridge approach by some teachers, low English literacy among students at the early stages, and the relatively high operational cost of the program. Therefore, adaptive managerial strategies, cross-sector collaboration, and a sustainable evaluation system are essential to ensure that this educational investment delivers a maximum impact on student outcomes and enhances the competitiveness of madrasah education both nationally and globally.